WAKAF TUNAI DAN PENGENTASAN KEMISKINAN - Bachrul Ulum (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
Cash waqf has become one of the important instruments in Islamic economics. Cash waqf has two functions. First, it functions as a medium for taqarrub (getting closer to Allah SWT) and secondly as a means to achieve prosperity and welfare of society. Management of cash waqf can be used as an instrument for poverty alleviation programs through sustainable investment. In this program, cash waqf will participate in government programs that are oriented towards community empowerment through cash for work. cash for work is an activity to empower rural communities, especially the poor and marginalized, which is productive by prioritizing the use of local resources, labor, and technology to provide additional wages / income, increase purchasing power, reduce poverty and so on. So that cash waqf has a strategic role in community financial empowerment. Keyword: Cash Waqf, Labor Intensive, Investment, Money